Effect of Low Versus High Tidal-Volume Total Liquid Ventilation on Pulmonary Inflammation - Sage, Michaël; See, Wendy; Nault, Stéphanie; Morin, Christophe; Michalski, Christina; Chabot, Benoit; Marouan, Sofia; Lavoie, Pascal M.; Micheau, Philippe; Praud, Jean-Paul; Fortin-Pellerin, Étienne (Frontiers in Physiology, 2020)
Animal experiments suggest that total liquid ventilation (TLV) induces less ventilator-induced lung injury (VILI) than conventional mechanical gas ventilation. However, TLV parameters that optimally minimize VILI in newborns remain unknown. Our objective was to compare lung inflammation between low (L-VT) and high (H-VT) liquid tidal volume and evaluate impacts on the weaning process. Sixteen anesthetized and paralyzed newborn lambs were randomized in an L-VT group (initial tidal volume of 10 mL/kg at 10/min) and an H-VT group (initial tidal volume of 20 mL/kg at 5/min). Five unventilated newborn lambs served as controls. After four hours of TLV in the supine position, the lambs were weaned in the prone position for another four hours. The levels of respiratory support needed during the four hours post-TLV were compared. The anterior and posterior lung regions were assessed by a histological score and real-time quantitative PCR for IL1B, IL6, and TNF plus 12 other exploratory VILI-associated genes. All but one lamb were successfully extubated within two hours post-TLV (72 ± 26 min vs. 63 ± 25 min, p = 0.5) with similar FiO2 at 4 hours post-TLV (27 ± 6 % vs. 33 ± 7 %, p = 0.3) between the L-VT and H-VT lambs. No significant differences were measured in histological inflammation scores between L-VT and H-VT lambs, although lambs in both groups exhibited slightly higher scores than the control lambs. The L-VT group displayed higher IL1B mRNA expression than the H-VT group in both anterior (2.8 ± 1.5-fold increase vs. 1.3 ± 0.4-fold increase, p = 0.02) and posterior lung regions (3.0 ± 1.0-fold change increase vs. 1.1 ± 0.3-fold increase, p = 0.002), respectively. No significant differences were found in IL6 and TNF expression levels. Gene expression changes overall indicated that L-VT was associated with a qualitatively distinct inflammatory gene expression profiles compared to H-VT, which may indicate different clinical effects. In light of these findings, further mechanistic studies are warranted. In conclusion, we found no advantage of lower tidal volume use, which was in fact associated with a slightly unfavorable pattern of inflammatory gene expression.